Biotechnological bases of the development of cloned pig embryos - A. V. Lopukhov; G. N. Singina; N. A. Zinovieva (Вавиловский журнал генетики и селекции, 2019)
The term ‘clone’ in animal biotechnology refers to an organism derived from non-sexual reproduction, which is both a direct offspring and a genetic copy of the parent organism. To date, the pig appears to be the most interesting object in cloning research. Somatic cell nuclear transfer in pigs has a wide range of potential applications in various fields of human scientific and economic activities. However, the efficiency of producing cloned embryos in swine is still lower than that of other livestock species, in particular horses and cattle. Somatic cell nuclear transfer is a technically complex multi-stage technology, at each stage of which the pig oocytes, which are more susceptible to changes of surrounding conditions, are affected by various factors (mechanical, physical, chemical). At the stage of oocyte maturation, changes in the cell ultrastructures of the ooplasm occur, which play an important role in the subsequent nuclear reprogramming of the transferred donor cell. Before transfer to the oocyte donor somatic cells are synchronized in the G0/G1 stage of the cell cycle to ensure the normal ploidy of the cloned embryo. When removing the nucleus of pig oocytes maturated in vitro, it is necessary to pay attention to the problem of preserving the viability of cells, which were devoid of their own nuclear material. To perform the reconstruction, a somatic cell is placed, using micro-tools, in the perivitelline space, where the first polar body was previously located, or in the cytoplasm of an enucleated oocyte. The method of manual cloning involves the removal of the oocyte nucleus with subsequent fusion with the donor cell without the use of micromanipulation techniques. The increased sensitivity of oocytes to the environmental conditions causes special requirements for the choice of the system for in vitro culture of cloned pig embryos. In this work, we have reviewed the modern methods used for the production of cloned embryos and identified the technological issues that prevent improving the efficiency of somatic cloning of pigs.